Left for dead eaudiobook My journey home from everest. - Weathers, Beck (Tantor Media, 2018)
In 1996 Beck Weathers and a climbing team pushed toward the summit of Mount Everest. Then a storm exploded on the mountain, ripping the team to shreds, forcing brave men to scratch and crawl for their lives. Rescuers who reached Weathers saw that he was dying, and left him. Twelve hours later, the inexplicable occurred. Weathers appeared, blinded, gloveless, and caked with ice—walking down the mountain. In this powerful memoir, now featuring a new preface, Weathers describes not only his escape from hypothermia and the murderous storm that killed eight climbers, but the journey of his life. This is the story of a man's route to a dangerous sport and a fateful expedition, as well as the road of recovery he has traveled since; of survival in the face of certain death, the reclaiming of a family and a life; and of the most extraordinary adventure of all: finding the courage to say yes when life offers us a second chance.